Nunsense [videorecording (DVD)] - Goggin, Dan (Distributed exclusively by Image Entertainment, Inc., 1998)
The Little Sisters of Hoboken are trying to raise money to bury a group of nuns accidentally poisoned by their own convent chef. You'll join the live audience watching the Sisters display their divine talents in a zany benefit revue.